2018
DOI: 10.1161/circresaha.117.311428
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-100 Suppresses Chronic Vascular Inflammation by Stimulation of Endothelial Autophagy

Abstract: Many attempts to modulate leukocyte-endothelial interaction to prevent or reduce excessive inflammatory reactions were made in the past. However, the basic regulatory principles of the endothelial inflammatory process remain unclear. It seems that the inhibition of individual components of the inflammatory cascade, for example, by a single antibody against an adhesion molecule, may not be enough to achieve a sustained effect on vascular inflammation.In the past years, microRNAs have been identified as importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 50 publications
5
78
0
1
Order By: Relevance
“…MicroRNAs (miRNAs) belong to a class of short noncoding regulatory RNAs (22–24 nucleotides) (Li et al, ; Treiber, Treiber, & Meister, ; Wang et al, 2015; Su et al, ), which exert their functions by binding to the 3' untranslated region (3' UTR) or protein coding sequence of target mRNAs (Frankel et al, ; Thomou et al, ). MiRNAs play crucial roles in regulating many metabolic diseases (Hanin et al, ; Langlet et al, ; Pankratz et al, ; Yu et al, ; Zhang et al, ). However, the role of miRNAs in the regulation of the aging‐associated metabolic phenotype is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) belong to a class of short noncoding regulatory RNAs (22–24 nucleotides) (Li et al, ; Treiber, Treiber, & Meister, ; Wang et al, 2015; Su et al, ), which exert their functions by binding to the 3' untranslated region (3' UTR) or protein coding sequence of target mRNAs (Frankel et al, ; Thomou et al, ). MiRNAs play crucial roles in regulating many metabolic diseases (Hanin et al, ; Langlet et al, ; Pankratz et al, ; Yu et al, ; Zhang et al, ). However, the role of miRNAs in the regulation of the aging‐associated metabolic phenotype is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have indicated that miRNAs can control a lot of fundamental biological processes (Rajman & Schratt, ; Zhang et al, ). For example, miR‐100 can inhibit chronic vascular inflammation by stimulating endothelial autophagy (Pankratz et al, ). miR‐126 can alleviate endothelial cells injury in atherosclerosis via inhibition of PI3 K/Akt/mTOR pathway (Tang & Yang, ).…”
Section: Introductionmentioning
confidence: 99%
“…miR‐100 is reported to suppress the regulation of IGF‐1R/mTOR pathway by directly targeting mechanistic target of rapamycin ( mTOR ), leading to inhibited cell growth and proliferation . A recent study by Pankratz et al., using both in vitro and in vivo models identified anti‐inflammatory effects of miR‐100 in vascular endothelium by suppressing endothelial adhesion molecule ( ICAM‐1, VCAM‐1 and E‐Selectin ) directly targeting two individual components of the mTORC1 complex ( mTOR and Raptor ). mTOR plays an important role in regulating cell growth .…”
Section: Discussionmentioning
confidence: 99%